A methods engineering study on Melawares Manufacturing Corp. - Catapang, Cyrus Dan (College of Engineering, 2004)
Melawares Manufacturing Corp. is the leading melamine manufacturer in the Philippines. It produces excellent products such as dinnerware, microwavable containers and Polyethylene Terephthalate (PET) bottles. The company sells its products in leading Department Stores, Fast Food Chains, Restaurants, Canteens, Shipping and Airline companies. The method study centered on the design section of the company. Data were gathered through interviews and actual observations in the workplace. These data were documented using tools and concepts in Methods Engineering. The group identified all problem areas using the Stream Diagnostic Diagram. The problems identified are delays in initial inspection, lack of personal safety equipment, repeated weighing due to usage of needle type weighing scale, poor housekeeping, insufficient space for cutting and trimming operations, poor material storage, no standard time, no minimum production requirement and under utilized workers. Problems were verified and evaluated. It is the task of the team to come up with possible solutions to the aforementioned problems. Feasible solutions or alternatives for each problem were identified and weighed against a specific criteria set by the team. The risks and threats of these alternatives against existing conditions were assessed. The alternatives, which have more desirable consequences as well as satisfy the objectives, were chosen as solutions. For the repeated weighing due to usage of needle type weighing scale, the chosen alternative is to purchase a digital weighing scale. With the new weighing scale, readings will more accurate and precise. The lack of personal safety equipment can be solved by providing first aid boxes around the area for immediate use in case of emergency. Hiring a janitor and buying enough cleaning materials for him to use can address poor housekeeping. For insufficient space for cutting and trimming section near the elevator. Proposed layout was made for the new space. Poor material storage can be solved by providing more racks or adding another level to the present racks to accomodate more decal designs. Conducting a continuous timing method can address the problem in not having time standards. No minimum production requirement can be solved by performing time study so as to set standards. The chosen alternatives are subject for implementation. The team also provided an implementation plan for the company. These plans may serve as a guide to the company in the implementation of the various changes brought about by the alternatives.